Bernières' immense burning glass - Cazin, Achille (The Phenomena and Laws of Heat, 1869)
Engraved plate illustrates M. de Bernières' immense burning glass, capable of causing combustion through the use of lenses and sunlight. Sunlight passes through two lenses projected onto a combustible surface causing it to ignite. More information can be found on page 82. This illustration comes from The Phenomena and Laws of Heat by Achille Cazin. Frontismatter and select illustrations have been digitized from this work on the laws of heat.
Keywords: Rich, Elihu, 1819-1875; Heat--Conduction; Bernières, M. de; Combustion; Scientific illustration